Pengaruh Tunjangan terhadap Kinerja Pegawai dengan Motivasi Kerja sebagai Variabel Moderasi pada Badan Pengelolaan Keuangan Aset Daerah Provinsi Papua - Minus Enembe; Muhamad Yamin Noch; Abdul Rasyid; Kartim (Journal of Economics Review (JOER), 2023)
The purpose of this study is to ascertain, at the Regional Financial and Asset Management Agency of Papua Province, the impact of benefits on employee performance using work motivation as a mediator. With 148 respondents overall, samples were gathered using the saturation sampling approach. Mediation is the analytical technique utilized. The study's findings demonstrate that the performance of employees of the Regional Financial and Asset Management Agency of Papua Province is positively and significantly impacted by performance bonuses. The Papua Province Regional Financial and Asset Management Agency's personnel perform better when they are motivated at work, which is a good and substantial effect. Work motivation is able to mediate the effect of performance allowances on employees of the Regional Financial and Asset Management Board of Papua Province in a positive and significant way. Performance allowances have a positive and significant impact on the performance of employees of the Regional Financial and Asset Management Board of Papua Province